INCENTIVE AND DISINCENTIVE FOR PROTECTION OF SUSTAINABLE FOOD AGRICULTURAL LAND IN CILEGON CITY - Cep Jandi Anwar; Tatang Sutisna; Asep Ridwan; Sirajuddin Sirajuddin (AGROINTEK, 2023)
This study examines the application of sustainable food on agricultural land in Cilegon City. This study also analyzes the factors contributing to land conversion, productivity issues, and incentives and disincentives for the protection of sustainable food agricultural land in Cibeber, Jombang, and Purwakarta districts. In Cilegon city, most of the sustainable food agricultural land areas are not owned by the local government but by citizens. This condition makes the land vulnerable to being converted by landowners for non-agricultural uses. The existence should be strengthened with space utilization control instruments as a technical rule to prevent agricultural land conversion from developing and violating the spatial designation determined in the spatial plan. This study uses a parallel mixed method namely in the form of spatial methods and qualitative methods. This study found the factors that determine agricultural incentives and disincentives in the three districts in Cilegon City so that these factors can be used in determining the types of incentives and disincentives influencing land owners to defend land his farm. The factors obtained are derived from the variable based on the literature review synthesis. The variable is asked to the respondents until the variables are consensus. The results showed some economic and non-economic factors that determine agricultural land conversions, such as farmers’ family necessities of life, housing development, and low agricultural land productivity. Some incentives for farmers can be supplied by providing services and infrastructure to support farmlands, such as irrigation, water jet pump, fertilizers and seeds, and marketing aid to protect agricultural land from conversion. Some disincentives, such as higher taxes and tighter building permits, should be imposed on agricultural land conversion. This study provides recommendations to protect sustainable food agricultural land. Furthermore, it promotes detailed agrarian reform and equalizes perceptions among Regional Apparatus Organizations. It also disseminates information to the community and updates the mapping of water sources. Finally, it promotes the issuance of local government law of Protection of Sustainable Food Agricultural land.